An Implementation of the SIESTA code for Electronic Simulations and Its Application in Ordinary Hexagonal Ices - Jan, Morrison; Jan, Morrison; N, Tsogbadrakh (Scientific transaction of the National University of Mongolia. Physics, 2022)
We consider descriptions of a Density Functional Theory (DFT), a flexible LCAO method, and an implementation of the SIESTA code for electronic simulations in crystalline solids. We have defined equilibrium lattice parameters and relaxed atomic positions of ordinary hexagonal iccs(disordered and ordered) with 16 water molecules by an Ab Initio total energy calculation using the SIESTA code. These results will be compared with the results of a plane wave (PW) ultrasoft-pscudopotential method by the CASTEP code.